Analisis Potensi dan Evaluasi Emisi Biodiesel dari Palm Oil Mill Effluent - Hariyadi, Tiara Puja; Jelita, Marhama (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2024)
The substantial development of the palm oil industry in Indonesia is evident in the high production of Crude Palm Oil (CPO) as the primary product and Palm Oil Mill Effluent (POME) as a byproduct in palm oil mills. POME waste contains emissions that can harm the environment, necessitating proper waste management. This issue can be addressed by transforming the waste into biodiesel, as it still contains Free Fatty Acids (FFA) and triglycerides. The utilization of biodiesel can reduce the reliance on fossil fuels and environmental pollution. The research aims to evaluate the quality of biodiesel based on the SNI 7182:2015 standard, considering parameters such as Free Fatty Acid (FFA), acid value, density, water content, and viscosity through experimental processes involving sulfuric acid esterification and basic catalyst transesterification. The study is expected to provide information on the potential of biodiesel as a vehicle fuel and energy source for colt diesel engines, along with an emission analysis during the transition from biodiesel to solar. The biodiesel produced meets the standards for FFA (0.26%), acid value (0.57 mg/KOH), and density (0.871 g/ml). The waste volume of 490 m3/day generates 5,096 liters/day of biodiesel, sufficient for 23 units of colt diesel engines with 55% efficiency, producing an energy output of 988,902.91 J. The transition to biodiesel fuel can reduce CO2 emissions by 20.4%, NOx by 50%, and HC by 40%.Keywords – Biodiesel, POME, Renewable Energy, Esterification